Mangemen Strategi Pelayanan BPBD Provinsi Jatim dalam Penanganan Masyarakat yang Terdampak Banjir Kota Surabaya - Agres Ade Laksamana; Sri Kamariyah; Ika Devy Pramudiana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the strategic management of disaster services in handling flood-affected communities in Surabaya City. This study uses a qualitative descriptive approach with an analytical framework of strategic management theory according to Wheelen and Hunger (2008), which includes four main stages: environmental observation, strategy formulation, strategy implementation, and evaluation and control. Data were obtained through documentation studies, field observations, and secondary data searches from official reports from the Regional Disaster Management Agency (BPBD), the Central Statistics Agency (BPS), and relevant online sources. The results show that the BPBD of East Java Province has implemented a systematic strategic management cycle in disaster services. During the environmental observation stage, the BPBD was able to identify the main threat in the form of the dominance of hydrometeorological disasters, particularly floods. During the strategy formulation stage, the BPBD established a mission, objectives, and strategic policies focused on disaster risk reduction, increasing community preparedness, and strengthening cross-sectoral coordination. Strategy implementation is realized through mitigation, preparedness, and emergency response programs, as well as the utilization of early warning systems and command centers. Meanwhile, evaluation and control are carried out continuously through monitoring disaster events and adjusting policies based on actual conditions in the field. The flood-affected community management strategy demonstrates a responsive and collaborative approach, despite still facing structural challenges such as tidal flooding and limited drainage infrastructure. This study concludes that implementing strategic management based on the theory of Wheelen and Hunger (2008) can improve the effectiveness of disaster services, but requires strengthening long-term mitigation and community empowerment.